The “Empty Cradle” Motif in Spanish Post-Romantic Lyrical Poetry - Cuvardic García, Dorde (2016)
The infant death has been, in the West, one of the main themes of lyrical poetry. And one of the motifs of this theme is the empty cradle, whose main discursive resource is the euphemistic circumlocution. In this article, we will first tour the poetry of infant death from the Golden Age to the twentieth century. Secondly, we will place the empty crib motif within the attenuation of pain caused by the death of a child. This goal is pursued by the culture of kitsch advocated by the bourgeoisie of the second half of the nineteenth century. The most important poetic expressions of the empty cradle motif, which boomed in the post-Romanticism, are also identified in this article. We end with a discussion of two known poems that express this motif, "The Empty Cradle" by Jose Selgas, and "Sweet Dream" by Rosalia de Castro.